2017
DOI: 10.1007/s12328-017-0743-2
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of 123I-metaiodobenzylguanidine by gastrointestinal stromal tumor

Abstract: A 52-year-old woman was admitted with a large intraabdominal mass. I- metaiodobenzylguanidine (I-MIBG) scintigraphy revealed considerable I-MIBG accumulation by the mass that was compatible with a diagnosis of paraganglioma. However, a spindle cell tumor that was identified using endoscopic ultrasound-guided fine needle aspiration before surgery was positive for CD117. The surgically resected mass was confirmed as a gastrointestinal stromal tumor (GIST). Although the mechanism ofI-MIBG uptake by GIST has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It has been reported that 123 I-MIBG may accumulate not only in neuroendocrine tumors but also in angiomyolipomas, renal cell carcinomas, hepatocellular carcinomas, adrenocortical adenomas, and adrenocortical carcinomas. Four GISTs with false-positive 123 I-MIBG scintigraphy findings have been previously described ( 6 ) ( Table 2 ). There were no relationships between the patient age, sex, or symptoms.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been reported that 123 I-MIBG may accumulate not only in neuroendocrine tumors but also in angiomyolipomas, renal cell carcinomas, hepatocellular carcinomas, adrenocortical adenomas, and adrenocortical carcinomas. Four GISTs with false-positive 123 I-MIBG scintigraphy findings have been previously described ( 6 ) ( Table 2 ). There were no relationships between the patient age, sex, or symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…The following two theories are considered the mechanisms underlying MIBG accumulation in GISTs ( 6 , 7 ). First, GISTs are believed to arise from interstitial cells of Cajal (ICCs).…”
Section: Discussionmentioning
confidence: 99%
“…MIBG scintigraphy is an effective diagnostic tool for the investigation of the cause of parkinsonism 1 and tumors, including paraganglioma, pheochromocytoma, and neuroblastoma, 2–4 because they originate from sympathetic ganglion cells. Other reports have described other tumors that show uptake of MIBG, including adrenocortical adenoma/carcinoma, hepatocellular carcinoma, and gastrointestinal stromal tumors 5–8 . Although lymphoma involving the adrenal gland is reported to demonstrate the uptake of MIBG, 9 it is not established that lymphoma in organs other than the adrenal glands shows increased uptake of MIBG.…”
mentioning
confidence: 99%
“…Other reports have described other tumors that show uptake of MIBG, including adrenocortical adenoma/carcinoma, hepatocellular carcinoma, and gastrointestinal stromal tumors. [5][6][7][8] Although lymphoma involving the adrenal gland is reported to demonstrate the uptake of MIBG, 9 it is not established that lymphoma in organs other than the adrenal glands shows increased uptake of MIBG. Here, we report a case of DLBCL showing the uptake of MIBG despite the absence of adrenal involvement.…”
mentioning
confidence: 99%
“…However, false-positive findings do occur in many different situations 6–8 . MIBG uptake in GIST have been reported before 9,10 . Recognizing abnormal activity caused by gastric GIST is important because gastric MIBG activity can be a normal variant 11 .…”
mentioning
confidence: 99%